2023
DOI: 10.3390/ijms24076441
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Curcumin on Oxidative Stress and Ferroptosis in Acute Ammonia Stress-Induced Liver Injury in Gibel Carp (Carassius gibelio)

Abstract: This study investigated the potential role of curcumin (CUR) in preventing oxidative stress and ferroptosis induced by ammonia exposure in gibel carp. Experimental fish (initial weight: 11.22 ± 0.10 g, n = 150) were fed diets supplemented with or without 0.5% CUR for 56 days, followed by a 24 h ammonia (32.5 mg/L) exposure. Liver damages (aspartate aminotransferase (AST), alanine aminotransferase (ALT), adenosine deaminase (ADA), and alkaline phosphatase (ALP)) and oxidative stress enzyme activities (reactive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 39 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…In the studies on drosophila , yeast, and nematodes, curcumin treatment was found to extend lifespan in association with enhanced SOD enzyme activity ( Zia et al, 2021 ; Utomo et al, 2022 ). By interacting with various antioxidant enzymes such as GPx and SOD, curcumin has the effect of reducing lipid peroxidation and preserving the active state of antioxidant enzymes ( Wu et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the studies on drosophila , yeast, and nematodes, curcumin treatment was found to extend lifespan in association with enhanced SOD enzyme activity ( Zia et al, 2021 ; Utomo et al, 2022 ). By interacting with various antioxidant enzymes such as GPx and SOD, curcumin has the effect of reducing lipid peroxidation and preserving the active state of antioxidant enzymes ( Wu et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…GPX4 is an important enzyme responsible for removing peroxides and hydroxyl radicals generated by LOX and PUFAs, thereby reducing lipid peroxidation [51,52]. In cases of acute ammonia exposure, hepatic gpx4 expression was suppressed, leading to the accumulation of lipid peroxides and the induction of ferroptosis [53]. In contrast, ACSL4, LPCAT3, and LOX are involved in fatty acid metabolism and promote lipid peroxidation, which are key factors affecting ferroptosis [54].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, curcumin (CUR) efficiently attenuated ammonia-induced oxidative damages and ferroptosis in gibel carp. 129 4.5.6. Cigarette Smoke (CS).…”
Section: House Dust Mites (Hdm)mentioning
confidence: 99%
“…These findings suggest that ammonia can trigger ferroptosis in fish macrophages, providing new insights into ammonia toxicity from a ferroptosis perspective. Interestingly, curcumin (CUR) efficiently attenuated ammonia-induced oxidative damages and ferroptosis in gibel carp …”
Section: Ferroptosis Inducers In Environmental Pollutantsmentioning
confidence: 99%